Evaluation of antibacterial, free radical scavenging activites and phytochemical composition of Boswellia dalzielii Hutch extracts - BOTHON, FIFA THEOMAINE DIANE; ABOU, Lydia; ATINDEHOU, MENONVE MEGNISSE (My University, 2019)
Ethanol extract and essential oil of Boswellia dalzielii leaves were screened for their antibacterial and antiradical activities by using microdilution and 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical methods respectively. Ethanol extract was submitted to a phytochemical screening and the essential oil to Gas Chromatography-Mass Spectrometry (GC/MS) analysis. Antibacterial studies reveal a MIC of 1.25 mg/ml for ethanol extract and 1.25 μl/ml of essential oil on Methicillin-resistant Staphylococcus aureus, but no MIC on Staphylococcus aureus. The essential oil was more powerful radical scavenging activity with EC50 value of 1.25 μg/mL which greater than the standard antioxidants, ascorbic acid (EC50 = 5 μg/mL). The phytochemical screening reveals the presence of metabolites mainly 3.56 ±0.06 mg GAE/ g of extract of total polyphenol and 1.24±0.01 mg QE/ g of extract. GC-MS results show the presence of: Zerumbone (33.69%), α-phellandrene (11.80%), alpha α-pinene (9.71%), Germacrene D (9.08%) ß - phellandrene (8.19%) and Trans ß – caryophyllene (7.45%) like major compounds. These compounds could be responsible for the antibacterial and scavenging activities.
Keywords: Boswellia dalzielii; extracts; MRSA; antioxidant